A CONTRIBUIÇÃO DA ARSO NO DESENVOLVIMENTO DE PROJETOS SUSTENTÁVEIS: Um estudo de caso - Segheto Júnior, Ivair (2010)
One of the challenges today is sustainable development, whether in the State, organizations and society. This study examines the concepts of development locality, the impacts of globalization and the role of society in sustainable development location. The planning and strategy development and municipal location, aspects of sustainability, its social and development objectives of the millennium round the base to verify the application of network society. The research is developed through case study applied to 42 leaders of society Linhares - ES, supported by the literature review and its problem-question: "what is the contribution of Arso in the development of sustainable projects?". In the treatment of the networks, you will need to identify local leaders. With the questionnaire, other leaders were given, where these respondents were next. Finally, the technique was utilized for analyzing social network (friendship, dating frequency and confidence). The data obtained allowed to examine a phenomenon in its natural environment, from multiple sources of evidence (individuals, groups, organizations) and identified a strong tendendcia community organizing through their leadership and desire to seek balanced development through phenomena related to this reality.